2018
DOI: 10.21315/jps2018.29.s2.15
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phenol from Bio-oil Produced by Pyrolysis of Coconut Shell

Abstract: Bio-oil from coconut shell pyrolysis has a very acidic pH and is corrosive due to the presence of phenolic compounds. Phenol is corrosive and can cause damage to the engine. If the bio-oil is intended to be used as an alternative diesel fuel, the phenol content needs to be removed. Phenol actually has an economic value that can be used as disinfectants, resins, pesticides, explosives, drugs and dyes. Separation of phenol from bio-oil can be carried out using liquid-liquid extraction method by utilising solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Biomass (organic material) can be acquired from forests, agricultural wastes, household wastes, plantations and industries. Hydrocarbon compounds contained in biomass could yield heat energy producing fuels (Fardhyanti and Damayanti, 2017; Montevecchi, 2016). Biomass holds promise as a good feedstock for generating liquid fuels in the imminent future (Demiral and Ayan, 2011; Ilknur et al., 2012; Donate, 2014; Joardder et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass (organic material) can be acquired from forests, agricultural wastes, household wastes, plantations and industries. Hydrocarbon compounds contained in biomass could yield heat energy producing fuels (Fardhyanti and Damayanti, 2017; Montevecchi, 2016). Biomass holds promise as a good feedstock for generating liquid fuels in the imminent future (Demiral and Ayan, 2011; Ilknur et al., 2012; Donate, 2014; Joardder et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study is in accordance with the study by Gresinta et al [38] and a comparative review by Dolah et al [39] where the highest component of bio-oil in OPEFB is phenol compounds. Meanwhile, high levels of phenol in bio-oil will affect the high viscosity and acid number which will cause corrosion, decrease the degree of acidity (pH) and reduce the heating value of bio-oil [40][41][42]. So it can be concluded that the low phenol content from the results of this study indicates that the research results are better than previous studies.…”
Section: Effect Of Zeolite Catalyst On Pyrolysis Productsmentioning
confidence: 57%
“…According to Fardhyanti et al [62], phenols required to be eliminated from bio-oil to lessen its corrosiveness. Using the liquid-liquid extraction technique and a solvent like methanol, phenol components from bio-oil could be removed.…”
Section: Bio-oil Upgrading Processmentioning
confidence: 99%